Prevalence of the persistent median artery in patients undergoing surgical open carpal tunnel release: A case series - Katarzyna Osiak; Pierre Elnazir; Agata Mazurek; Artur Pasternak (Elsevier, 2021)
Background: Carpal tunnel syndrome is a common condition in adults with an estimated prevalence of up to 5% in the general population. The presence of a persistent median artery is an important consideration for plastic and orthopedic surgeons who frequently perform carpal tunnel release. This artery may persist into adulthood and constitute a significant supply of blood to the hand, sometimes compressing the median nerve. Purpose: In this case series, we describe the prevalence of the persistent median artery identified intraoperatively in Polish subjects undergoing surgical open carpal tunnel release. Methods: The data regarding the prevalence of persistent median artery were retroactively collected postoperatively from the standard surgical protocols. Results: Persistent median artery was identified in 36 out of 1285 operated hands (2.8%). The observed PMAs were identified in 15 (2.0%) cases out of 750 right upper limbs and in 21 (3.9%) cases out of the 535 left upper limbs. Conclusions: Persistent median artery can be present in the operating field of any surgeon that performs carpal tunnel release and any other surgical procedures in the wrist region. Therefore awareness of its presence is crucial to minimize intraoperative complications such as bleeding or digital ischemia.